THE STUDENTS’ LEARNING STRATEGIES IN INCREASING SKILLS - Ahmad Syaifurrohman Chilmy; Sri Endang Kusmaryati; Aisyah Ririn Perwikasih Utari (Universitas Muria Kudus, 2020)
Learning strategy is an individual way or specific behavior in action of getting and processing information to make them comfortable in learning situations to improve their progress in learning proccess. This study aims to identify the direct and indirect learning strategies of the students of Muria Kudus University. This is a qualitative descriptive research conducted in the third semester of Muria Kudus University English Education Department Teacher Training and Educational Faculthy. The subjects of this study were the third semester students in the academic year 2016/2017. The result indicates that the students prefer to use indirect learnings strategies with average score = 3.4822 than direct learning strategies with average score = 3.2987. The direct learning strategies that students used to increase their English skills were cognitive strategies with the average score = 3.3765, the compensation strategies with the average score = 3.3738, and the memory strategies with the lowest average score = 3.1460. Indirect learning strategies used by the students was social stratgies with the average score=3.5976, the metacognitive strategy with the average score=3.573, and the afective strategies with the average score = 3.2761.